The perception of state university academics on the influence of floral therapy and placebo on their anxiety disorder (Research, Society and Development, 2020)
The student experiences several confrontations that can trigger anxiety disorders. Physiotherapy has additional features that can treat anxiety, such as flower therapy. Therefore, the objective of the study was to analyze the perception of academics of a state university about the influence of flower therapy and placebo on their anxiety disorder. To do so, conduct a qualitative exploratory study with recorded and fully transcribed interviews was conducted based on a guiding question: “What did you notice in your daily life with the use of the compost”? The study population was composed by 37 academics of both genders, between 18 and 30 years old. The students were divided into the Treatment Group (Minas System Examination Formula) and the Placebo Group (water and preservative). The academics answered the guiding question after fully using the flask. From the reports presented, it was noticeable that both the use of the flower formula and the placebo lad to positive responses to anxiety symptoms, however, the answers provided by the treatment group were much more specific.